Entamoeba histolytica Trophozoites Induce a Rapid Non-classical NETosis Mechanism Independent of NOX2-Derived Reactive Oxygen Species and PAD4 Activity - Díaz-Godínez, César; Fonseca, Zayda; Néquiz, Mario; Laclette, Juan P.; Rosales, Carlos; Carrero, Julio C. (Frontiers in Cellular and Infection Microbiology, 2018)
Neutrophil extracellular traps (NETs) are DNA fibers decorated with histones and antimicrobial proteins from cytoplasmic granules released into the extracellular space in a process denominated NETosis. The molecular pathways involved in NETosis have not been completely understood. Classical NETosis mechanisms involve the neutrophil elastase translocation to nucleus due to the generation of reactive oxygen species (ROS) by NADPH oxidase (NOX2) or the peptidyl arginine deiminase 4 (PAD4) activation in response to an increase in extracellular calcium influx; both mechanisms result in DNA decondensation. Previously, we reported that trophozoites and lipopeptidophosphoglycan (LPPG) from Entamoeba histolytica trigger NET release in human neutrophils. Here, we demonstrated in a quantitative manner that NETs were rapidly form upon treatment with amoebic trophozoites and involved both nuclear and mitochondrial DNA. NETs formation depended on amoeba viability as heat-inactivated or paraformaldehyde-fixed amoebas were not able to induce NETs. Interestingly, ROS were not detected in neutrophils during their interaction with amoebas, which could explain why NOX2 inhibition using apocynin did not affect this NETosis. Surprisingly, whereas calcium chelation reduced NET release induced by amoebas, PAD4 inhibition by GSK484 failed to block DNA extrusion but, as expected, abolished NETosis induced by the calcium ionophore A23187. Additionally, neutrophil elastase translocation to the nucleus and serine-protease activity were necessary for NET release caused by amoeba. These data support the idea that E. histolytica trophozoites trigger NETosis by a rapid non-classical mechanism and that different mechanisms of NETs release exist depending on the stimuli used.